Optimasi Pengembangan Kelembagaan Industri Pangan Organik Di Jawa Timur - Krisno Budiyanto, Moch. Agus (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
The objective of this study is to identify optimalization of industries institutional development of organic food in East Java. The type of research used in this research is the study of phenomenology. Subjects of research is industries of organic food institution included UMKM for organic food, Department of Agriculture, Food Industry, Organic Food Farmers Group, and Banking in Lumajang District, Malang District and Blitar District in East Java Province. Data collection methods used are indepth interviews and participation observation. Test the validity of data used is the triangulation of sources and methods. The research data were analyzed with qualitative analysis (Content Analysis) by using the interactive model of Miles and Huberman. From the research results, it can be conclude that the pattern of industries institutional development of organic food in East Java divided into three optimize patterns namely the cluster pattern, the pattern of partnerships, and the pattern of BDSP (Business Development Services Provider). The clusters pattern is the industries institutional development of organic food with organic food way of grouping institutions (including UMKM) in a region or set the region as a specific business area. A partnership consisting of the core plasma partnerships and foster father partnerships. BDSP pattern is a pattern based development institution in the system of business development services. In general, the cluster pattern can improve the performance of the supply, distribution, marketing, and utility of industries of organic food in East Java. Lumajang District is the most potential area in the development of cluster patterns industries of oganic food.